2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037376
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical activation while viewing urban and garden scenes: A pilot fNIRS study

Abstract: Recent studies have shown that pleasant and unpleasant emotions could be detected through functional Near-Infrared Spectroscopy (fNIRS). This study investigates the prefrontal cortical activation in human subjects while they were viewing urban and garden scenes. A multi-channel continuous wave fNIRS system was used to record the prefrontal cortical activations from seven subjects. During the data collection, the subjects viewed 40 trials of video clips. In each trial, the subjects viewed a video of randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Functional near‐infrared spectroscopy (fNIRS) is a non‐invasive neuroimaging technology that maps the functions of the cerebral cortex by measuring hemodynamics and demonstrates cost‐effectiveness (Lai, Ho, Lim, & Ho, ). A recent fNIRS study showed that urban scene led to significant increase of oxyhemoglobin on the right area of the prefrontal cortex as compared to the garden scene (Yu, Ang, Ho, Sia, & Ho, ) and further research is required to assess the effect of plant viewing by fNRIS. However, we do not have a full understanding of the various EEG results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional near‐infrared spectroscopy (fNIRS) is a non‐invasive neuroimaging technology that maps the functions of the cerebral cortex by measuring hemodynamics and demonstrates cost‐effectiveness (Lai, Ho, Lim, & Ho, ). A recent fNIRS study showed that urban scene led to significant increase of oxyhemoglobin on the right area of the prefrontal cortex as compared to the garden scene (Yu, Ang, Ho, Sia, & Ho, ) and further research is required to assess the effect of plant viewing by fNRIS. However, we do not have a full understanding of the various EEG results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the psychological benefits of greenery for older adults are significant (i.e., decreased anxiety), and an indoor green environment can enhance spiritual health (Qin, Sun, Zhou, Leng, & Lian, 2014 (Lai, Ho, Lim, & Ho, 2017). A recent fNIRS study showed that urban scene led to significant increase of oxyhemoglobin on the right area of the prefrontal cortex as compared to the garden scene (Yu, Ang, Ho, Sia, & Ho, 2017) and further research is required to assess the effect of plant viewing by fNRIS. However, we do not have a full understanding of the various EEG results.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that exposure to nature, presumably found in many parks, promotes health across the lifespan also bolsters the practice of park prescriptions [19][20][21][22]. The biological basis for park prescriptions is further suggested by research that viewing urban versus garden scenes resulted in an increase of oxy-hemoglobin on the right area of the prefrontal cortex that indicates more stressful experience in the urban scenes [23].…”
Section: Ofmentioning
confidence: 98%
“…Control is often used, such as being in an urban environment, where a negative effect on the psychological and physiological well-being of the subjects has been observed [50]. Another way to assess the impact of the forest environment on humans is to simulate the impact of this environment in controlled conditions, for example by reproducing the images and sounds that occur in a forest environment, using a monitor [51], or by using virtual reality [52]. In this case, the control environment can be an image, a sound or virtual reality depicting the urban environment.…”
Section: Virtual Nature Environmentsmentioning
confidence: 99%